Exploring software defined networks for seamless handovers in vehicular networks - Silva, Miguel (2022)
With the growing interest in autonomous driving, constant connectivity for vehicles is becoming essential to enable the complete knowledge of the surrounding area, transmit and receive data that is crucial for the autonomous control. The vehicle mobility results in frequent service interruptions, and therefore, seamless handovers are required to mitigate this problem. Several IP-based solutions have been proposed in the literature, but they require tunneling approaches, which present excessive signaling and data overhead, service delay, and packet loss. One of these approaches, the NEMO-enabled Proxy Mobile IPv6 (N-PMIPv6) architecture, supports transparent handovers and simultaneous multi-homing, but at the cost of a high complexity and network overhead. This work explores the flexibility of Software Defined Networks (SDNs) in the management of a Vehicular Ad-hoc NETwork (VANET). In particular, the SDN concept is used to provide a seamless horizontal handover for the vehicle and its end-users. Two different SDN architectures are proposed, evaluating the impact of the depth of the softwarization environment. Real vehicular hardware and emulated mobility scenarios are used in the evaluation process where different application services are exploited. Results show that the lower complexity of the SDN solution allows for a better performance during a handover in a VANET, in terms of delays, packet losses and network overhead, making it seamless for the vehicles and its users.